PKM PENYULUHAN DAN LATIHAN FISIOTERAPI PADA CEDERA ACL S CEDERA ACL DI SPORT CENTER RS AWAL BROS PEKANBAR) - Geza, Romi Tria; Wijanarko, Wahyu; Sulaiman, Sulaiman (MAJU : Indonesian Journal of Community Empowerment, 2024)
The community service program titled "PKM: Physiotherapy Counseling and Training on ACL Injuries at Sport Center RS Awal Bros Pekanbaru" aimed to provide education and training for 20 athletes with anterior cruciate ligament (ACL) injuries. This program included sessions on injury prevention strategies, strengthening exercises, and post-injury rehabilitation techniques to enhance recovery and performance. Each participant received hands-on training from experienced physiotherapists, focusing on safe practices to prevent future injuries and improve mobility. The program's outcomes showed improvements in participants' understanding and ability to perform recommended exercises independently, reflecting the effectiveness of physiotherapy-based interventions in managing ACL injuries.